HIV Broadly Neutralizing Antibodies Expressed as IgG3 Preserve Neutralization Potency and Show Improved Fc Effector Function - Richardson, Simone I.; Ayres, Frances; Manamela, Nelia P.; Oosthuysen, Brent; Makhado, Zanele; Lambson, Bronwen E.; Morris, Lynn; Moore, Penny L. (Frontiers in Immunology, 2021)
The ability of several broadly neutralizing antibodies (bNAbs) to protect against HIV infection is enhanced through Fc receptor binding. Antibody isotype modulates this effect, with IgG3 associated with improved HIV control and vaccine efficacy. We recently showed that an IgG3 variant of bNAb CAP256-VRC26.25 exhibited more potent neutralization and phagocytosis than its IgG1 counterpart. Here, we expanded this analysis to include additional bNAbs targeting all major epitopes. A total of 15 bNAbs were expressed as IgG1 or IgG3, and pairs were assessed for neutralization potency against the multi-subtype global panel of 11 HIV strains. Binding to the neonatal Fc receptor (FcRn) and Fcγ receptors were measured using ELISA and antibody-dependent cellular cytotoxicity (ADCC) and phagocytosis were measured using infectious viruses and global panel Env SOSIP trimers, respectively. IgG3 bNAbs generally showed similar or increased (up to 60 fold) neutralization potency than IgG1 versions, though the effect was virus-specific. This improvement was statistically significant for CAP256-VRC26.25, 35022, PGT135 and CAP255.G3. IgG3 bNAbs also showed significantly improved binding to FcγRIIa which correlated with enhanced phagocytosis of all trimeric Env antigens. Differences in ADCC were epitope-specific, with IgG3 bNAbs to the MPER, CD4 binding site and gp120-gp41 interface showing increased ADCC. We also explored the pH dependence of IgG1 and IgG3 variants for FcRn binding, as this determines the half-life of antibodies. We observed reduced pH dependence, associated with shorter half-lives for IgG3 bNAbs, with κ-light chains. However, IgG3 bNAbs that use λ-light chains showed similar pH dependence to their IgG1 counterparts. This study supports the manipulation of the constant region to improve both the neutralizing and Fc effector activity of bNAbs, and suggests that IgG3 versions of bNAbs may be preferable for passive immunity given their polyfunctionality.